The coconut oil miracle - Fife, Bruce, 1952- (Avery, a member of Penguin Group (USA), 2013)
For years, The Coconut Oil Miracle has been a reliable guide for men and women alike. Now in its fifth edition, this revised and updated version has even more information on the benefits of coconut oil and shows readers how to use it for maximum effect, including a nutrition plan with 50 delicious recipes. Coconut oil is much more than just a fad. It is a uniquely curative elixir that has been shown to have countless health benefits. When taken as a dietary supplement, used in cooking, or applied directly to the skin, coconut oil has been found to: Promote weight loss Help prevent heart disease, cancer, diabetes, arthritis, Alzheimer's, and many other degenerative diseases Strengthen the immune system Improve digestion Prevent premature aging of the skin Beautify skin and hair.